Improving the Outcomes in Oncological Colorectal Surgery - Iqra, Sheeren, Zareen Tarique, Musarat Nazir, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the improvement in the outcomes in oncological colorectal surgery. Study Design: Prospective study, Place & duration of study: Department of General Surgery, LUMHS Jamshoro from 1st January 2020 to 31st December 2022. Methodology: One hundred and fifty cases of colorectal cancer undergoing surgery were enrolled. They were multidisciplinary requiring compliance of surgeons at the operating room with their surgical teams. These interventions were based on sequential implementation of the evidence-based surgical site infection bundle (SSIB) and enhanced recovery after surgery (ERAS) protocols for all the patients undergoing colorectal surgery. Primary outcomes evaluated were duration of hospital stay as well as rate of complication in accordance with wound healing. Inverse proportional-weighting method was used for controlling possible variance within groups. The secondary outcome measures post improvement strategies were mortality within day 30, readmission within same period (30 days) or unplanned return to the operating table as well as numerous related complications. Results: The mean age of the cases in group A (pre-ERAS or pre-SSIB) was 61.2±10.9 years while in group B (pre-ERAS or post-SSIB) was 61.8±9.9 years and the mean age of Group C (post-ERAS or post-SSIB) was 63.7±10.1 years. There were more females within three groups such as 60%, 56% and 54% respectively than males. Hospital stay was highest within group A. The 30 days outcomes showed that the outcomes in group A showed highest number of death, wound infection and blood transfusion however the difference was insignificant for all other variable except wound infection. Conclusion: The subsequent addition of quality improvement within groups added positive outcomes in patients of oncological colorectal surgery with reduction in mortality, hospital stay as well as wound infection. Key words: Outcome, Colorectal carcinoma, Mortality, Hospital stay, Wound infection